2019
DOI: 10.1038/s41598-019-41876-w
|View full text |Cite
|
Sign up to set email alerts
|

Acute exposure to diesel exhaust induces central nervous system stress and altered learning and memory in honey bees

Abstract: For effective foraging, many insect pollinators rely on the ability to learn and recall floral odours, behaviours that are associated with a complex suite of cellular processes. Here, we investigated how acute exposure to a high-dose of diesel exhaust (containing 19.8 and 17.5 ppm of NO and NO 2 , respectively) affected associative learning behaviour of honey bees ( Apis mellifera ) and expression of a ubiquitous heat shock protein, HSP70, in their central nervous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…The brain is highly sensitive to glucocorticoids, such as cortisol, which is a stress hormone with important roles in cognition and depression. The response to stress starts in the CNS and acts via the hypothalamus and pituitary gland to increase the secretion of cortisol from the adrenal cortex (17,41). Recent epidemiological research revealed the correlation between air pollution and cortisol levels, and that NO 2 , PM2.5, and PM10 were reportedly associated with high wake-up cortisol (42,43).…”
Section: Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The brain is highly sensitive to glucocorticoids, such as cortisol, which is a stress hormone with important roles in cognition and depression. The response to stress starts in the CNS and acts via the hypothalamus and pituitary gland to increase the secretion of cortisol from the adrenal cortex (17,41). Recent epidemiological research revealed the correlation between air pollution and cortisol levels, and that NO 2 , PM2.5, and PM10 were reportedly associated with high wake-up cortisol (42,43).…”
Section: Depressionmentioning
confidence: 99%
“…DEP is neurotoxic only to neurons co-cultured with microglial cells and not to neurons alone. Further, these effects are reversible when the microglial cells involved are treated with pioglitazone, an antagonist of the peroxisome proliferatoractivated receptor-gamma (PPAR-γ) (41). PPARs are known to be ligand-activated transcription factors, regulating genes essential for various metabolic processes and cell differentiation, but also exerting anti-inflammatory actions after brain injury or in neurodegenerative diseases (92).…”
Section: Pathophysiological Mechanisms In the Nervous Systemmentioning
confidence: 99%
“…Another study has confirmed that the memory of honey bees has decreased within the time when they directly exposure to gas diesel exhaust (Reitmayer et al, 2019).…”
Section: The Effect Of Time On Honey Bee Memorymentioning
confidence: 80%
“…However, their benefits to pollinators can be reduced by heavy traffic pollution and summer verge cutting (Phillips et al 2019). Diesel exhaust pollution has been shown to affect bee olfaction and reduce flower detection due to negative impacts on learning and memory (Lusebrink et al 2015;Reitmayer et al 2019). Conversely reduced mowing frequency could enhance biodiversity, aesthetics and pollination services, whilst delivering costs savings, thereby potentially being acceptable to the public (O'Sullivan et al 2017).…”
Section: Enhancing the Wider Landscapementioning
confidence: 99%